Lactate in the critically ill patients: an outcome marker with the times - Nguyen, H Bryant (BioMed Central, 2011)
Lactic acid was first discovered in human blood in 1843. Since then it has been used as a prognosticator of outcome in critical illness. Regardless of its etiology, lactate's presence and trend over time have been shown to be independently associated with mortality. Two dynamic lactate measures, the time-weighted average lactate and the absolute change in lactate over the first 24 hours in the ICU, were recently shown to be better than static lactate measurements in predicting hospital and ICU deaths.